Mental health and continuity of care in healthcare centers in a city of Southeastern Brazil - Oliveira, Graziella Lage; Caiaffa, Waleska Teixeira; Cherchiglia, Mariangela Leal (Revista de Saúde Pública, 2008)
OBJECTIVE: To analyze factors associated with the continuity of mental health care provided for patients referred to healthcare centers. METHODS: A follow-up study was carried out with 98 patients assisted between 2003 and 2004. These patients were referred to eight healthcare centers with mental health teams located in the catchment area of a mental health reference venter in the city of Belo Horizonte, Southeastern Brazil. Social, demographic, clinical and continuity variables were described and then compared using the chi-square test. RESULTS: After referral, 35 patients did not attend the first visit in the healthcare center. Of those who did, 38 continued in treatment. To return to the reference center for a new visit after referral and to have had more than two referrals were factors that facilitated continuity of care. No individual characteristic was associated with continuity. CONCLUSIONS: The findings suggest that there is a gap in the proposal for the line of care. Treatment continuity seems to be more related to service factors than to patients' characteristics.